Humerus shape evolved in cetaceans under relaxed selection and random drift - Maria Ghazali; Svitozar Davydenko; Valeriia Telizhenko; Pavlo Otriazhyi; Karina Vishnyakova; Maia Bukhsianidze; Azucena Solis-Añorve; Igor Dzeverin; Pavel Gol’din (Communications Biology)
Abstract Mammalian humerus shape is mostly predicted by loading. This constraint is lifted for cetaceans and, therefore, can reflect other, specific evolutionary trends. To test this hypothesis, the three-dimensional shape of the humerus for 36 taxa of extinct and extant cetaceans was analyzed. The shape variance concurs with the evolution of diverging baleen and toothed whales and is independent of allometry. It shows traits associated with aquatic locomotion: humeral head twist, diaphysis shortening and straightening, and epiphyses enlargement. Also, changes in the anatomy of the humeral head and greater tubercle, modularity and integration patterns are associated with phylogeny. We suggest relaxed negative selection and random drift as the likely main evolutionary patterns for the evolution of the humerus shape. The evolution of genes regulating the humerus shape corresponds to the anatomical transformations and shows relaxed selection, site-level positive selection and nonsense mutations in cetaceans. Overall, the observed pattern well illustrates a “fly in a tube model” and shows its importance as a framework of emerging evolutionary innovations.